Impact of Self-Talk among University Futsal Player in University of Putra Malaysia: A Qualitative Approach - Jakiwa, Jorrye; Geok, Soh Kim; Fauzee, Mohd Sofian Omar (ASPENSI, 2015)
ABSTRACT: One of the approaches often used by athletes in order to improve psychological ability is self-talk. Self-talk is the internal language of self. Psychologist states that self-talk can influence factors such as confidence, enthusiasm, diligence, concentration, and strength, as well as reduce anxiety. The purpose of this study was to examine the effects of positive self-talk on performance among futsal players in University of Putra Malaysia. All of the eight respondents were males age between 21â24 (22.13 Â± 1.13) years of age, who agreed to participate in this qualitative study. Each of the subject agreed to be interviewed and to have their interview sessions recorded using an audio recorder. For the data interpretation, each of the recording was transcribed and coded by three researchers to determine the main themes of the attributes of self-talk among futsal players. As a result, there are five main themes that were generated from the whole interviews, namely: motivation, focus, effort (hard work), anxiety control, and encouragement. As a conclusion, the main effect of using self-talk among university futsal players is not only to increase motivation, encouragement, and anxiety control, but also to gain the spirit of hard work and improve focusing. KEY WORD: Self-talk, qualitative study, futsal players, motivation, focus, hard work, anxiety control, and encouragement.INTISARI: âKesan Kata Kendiri diantara Pemain Futsal Universiti di Universiti Putra Malaysia: Satu Pendekatan Kualitatifâ. Salah satu pendekatan yang kerap digunakan oleh ahli sukan untuk meningkatkan keupayaan psikologi adalah kata kendiri. Kata kendiri adalah bahasa dalaman diri. Ahli psikologi menyatakan bahawa kata kendiri boleh mempengaruhi faktor-faktor seperti keyakinan, semangat, ketekunan, tumpuan, dan kekuatan, serta juga mengurangkan keresahan. Tujuan kajian ini adalah untuk mengkaji kesan kata kendiri secara positif terhadap prestasi dalam kalangan pemain futsal di Universiti Putra Malaysia. Kesemua lapan responden adalah lelaki berumur antara 21-24 (22.13 Â± 1.13) tahun, yang bersetuju untuk mengambil bahagian dalam kajian kualitatif ini. Setiap seorang daripada subjek bersetuju untuk ditemubual dan sesi temubual mereka dirakam menggunakan perakam audio. Untuk tafsiran data, setiap rakaman disalin dan dikodkan oleh tiga penyelidik untuk menentukan tema utama berkenaan kata kendiri di kalangan pemain futsal. Hasilnya, terdapat lima tema utama yang dihasilkan daripada keseluruhan temubual, iaitu: motivasi, fokus, usaha (bekerja keras), kawalan kebimbangan, dan galakan. Kesimpulannya, kesan utama menggunakan kata kendiri antara pemain futsal universiti bukan sahaja untuk meningkatkan motivasi, dorongan, dan kawalan kebimbangan, tetapi juga untuk mendapatkan semangat kerja keras dan meningkatkan tumpuan.KATA KUNCI: Kata kendiri, kajian kualitatif, pemain futsal, motivasi, fokus, bekerja keras, kawalan kebimbangan, dan galakan.Â Â Â Â About the Authors:Â Jorrye Jakiwa is a Ph.D. Candidate at the UMS (Malaysia University of Sabah) in Kota Kinabalu, Sabah, Malaysia; Dr. Soh Kim Geok is an Associate Professor at the Department of Sports Studies UPM (University of Putra Malaysia) in Serdang, Selangor, Malaysia; and Dr. Mohd Sofian Omar Fauzee is a Professor at the School of Education and Modern Languages, College of Art and Sciences UUM (University of Utara Malaysia) in Sintok, Kedah, Malaysia. For academic purposes, the authors are able to be contacted via his/her e-mails address at: jorryejakiwa@yahoo.com, kimgeoks@yahoo.com, and mohdsofian@uum.edu.myHow to cite this article? Jakiwa, Jorrye, Soh Kim Geok & Mohd Sofian Omar Fauzee. (2015). âImpact of Self-Talk among University Futsal Player in University of Putra Malaysia: A Qualitative Approachâ in SIPATAHOENAN: South-East Asian Journal for Youth, Sports & Health Education, Vol.1(1) April, pp.1-8. Bandung, Indonesia: Minda Masagi Press, APAKSI Bandung, and KEMENPORA RI Jakarta, ISSN 2407-7348.Â Chronicle of the article: Accepted (January 27, 2015); Revised (March 5, 2015); and Published (April 21, 2015).